2020
DOI: 10.3390/pharmaceutics12090857
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Catanionic Vesicles from Arginine-Based Surfactants: A New Strategy to Tune the Antimicrobial Activity and Cytotoxicity of Vesicular Systems

Abstract: Their stability and low cost make catanionic vesicles suitable for application as drug delivery systems. In this work we prepared catanionic vesicles using biocompatible surfactants: two cationic arginine-based surfactants (the monocatenary Nα-lauroyl-arginine methyl ester—LAM and the gemini Nα,Nϖ-bis(Nα-lauroylarginine) α, ϖ-propylendiamide—C3(CA)2) and three anionic amphiphiles (the single chain sodium dodecanoate, sodium myristate, and the double chain 8-SH). The critical aggregation concentration, colloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…It was shown that cationic antimicrobial lipopeptides can be effective in the treatment of wound bacterial infection without adverse effects on porcine skin [ 83 ]. Recent studies on antimicrobial arginine-based gemini surfactants indicate an interesting possibility to incorporate them into vesicles together with anionic amphiphiles (catanionic vesicles), resulting in improved selectivity [ 84 ]. On the other hand, cationic micelles and liposomes injected intravenously into rats result in DNA damage in lungs and spleen [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that cationic antimicrobial lipopeptides can be effective in the treatment of wound bacterial infection without adverse effects on porcine skin [ 83 ]. Recent studies on antimicrobial arginine-based gemini surfactants indicate an interesting possibility to incorporate them into vesicles together with anionic amphiphiles (catanionic vesicles), resulting in improved selectivity [ 84 ]. On the other hand, cationic micelles and liposomes injected intravenously into rats result in DNA damage in lungs and spleen [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ζ-potential value of this formulation is negative and the interaction with the also negatively charged bacterial membrane is hindered. Recent studies revealed that the antibacterial efficiency of catanionic vesicles prepared with gemini arginine-based surfactants depends on the anionic/cationic ratio of the formulations [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained in this work agree with those obtained recently for catanionic systems prepared with arginine-based gemini surfactants. In Pinazo et al [ 33 ], it was found that the hemolytic activity of these formulations mainly depended on the proportion of cationic surfactant. Moreover, it was also observed that the incorporation of cholesterol into the catanionic vesicles resulted in a significant decrease in their hemolytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although catanionic vesicles have a huge applicability in biomedicine, they can suffer safety problems due to their eventual low bio-and emocompatibility. Numerous ongoing researches point to the optimization of their morphology, hydrophobicity, and ionic charge by carefully choosing the proper surfactant and by tuning the anionic/cationic surfactant ratio eventually adding some suited additive [218].…”
Section: Catanionic Vesiclesmentioning
confidence: 99%